1997
DOI: 10.3164/jcbn.22.163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Starvation on Antioxidant Enzymes and Respiratory Mitochondrial Functions in Kidney and Liver from Rats.

Abstract: SummaryThe influence of the nutritional status on the antioxidant defence system and on the mitochondrial respiratory functions of rat kidney and liver was studied. For that purpose, the antioxidant enzymes catalase, glutathione peroxidase, glutathione reductase, glutathione Stransferase, superoxide dismutase, the total glutathione and the respiration rates of states 3 and 4, the respiratory control ratio, and ADP/O ratio were measured before and after 2 and 4 days of starvation. The behaviour of the enzymes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
0
1
Order By: Relevance
“…The effect of starvation on mitochondrial properties is also likely to depend on both the tissue (Trzcionka et al 2008;Brown et al 2012;Crescenzo et al 2012) and the animal species involved (Emel'yanova et al 2007;Bottje and Carstens 2009). A reduction in the apparent P/O ratio in the liver of the food-deprived fish is consistent with previous studies of chickens (Bobyleva-Guarriero et al 1984), but contrasts with results found in the skeletal muscle of starving penguins (Monternier et al 2014) and in the livers of starved rats (Jung and Henke 1997). The degree to which mitochondrial properties change may also depend on the severity of the energetic challenge, for example, the duration of food deprivation (Hung et al 1997;Salin et al 2010b).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The effect of starvation on mitochondrial properties is also likely to depend on both the tissue (Trzcionka et al 2008;Brown et al 2012;Crescenzo et al 2012) and the animal species involved (Emel'yanova et al 2007;Bottje and Carstens 2009). A reduction in the apparent P/O ratio in the liver of the food-deprived fish is consistent with previous studies of chickens (Bobyleva-Guarriero et al 1984), but contrasts with results found in the skeletal muscle of starving penguins (Monternier et al 2014) and in the livers of starved rats (Jung and Henke 1997). The degree to which mitochondrial properties change may also depend on the severity of the energetic challenge, for example, the duration of food deprivation (Hung et al 1997;Salin et al 2010b).…”
Section: Resultssupporting
confidence: 81%
“…), but contrasts with results found in the skeletal muscle of starving penguins (Monternier et al. ) and in the livers of starved rats (Jung and Henke ). The degree to which mitochondrial properties change may also depend on the severity of the energetic challenge, for example, the duration of food deprivation (Hung et al.…”
Section: Resultscontrasting
confidence: 62%